Real‐world safety and effectiveness of pembrolizumab in Japanese patients with radically unresectable melanoma: An all‐case postmarketing surveillance in Japan. Issue 11 (27th July 2022) - Yamazaki, Naoya; Shimizu, Akiko; Ozaki, Masahiko; Hamada, Masahiro; Takeuchi, Noriko; Ito, Yuichiro; Maekawa, Shinichiroh
Abstract: This all‐case postmarketing surveillance (PMS) survey (101 centers; February 15, 2017, to March 3, 2020) captured factors that impact the safety and effectiveness of newly initiated pembrolizumab monotherapy for the treatment of radically unresectable melanoma in Japan. Eligible patients were enrolled both retrospectively and prospectively, and followed up at 1, 3, 6, and 12 months. Safety assessments included treatment‐related adverse events (TRAEs), adverse events of special interest (AEOSIs) from the Japanese Risk Management Plan (J‐AEOSIs), and J‐AEOSIs related to pembrolizumab. Effectiveness assessments included objective response rate (ORR; complete response/partial response) and disease control rate (DCR) according to the RECIST criteria. Overall, 294 and 236 patients comprised the safety and effectiveness (RECIST) assessment sets, respectively. Median (range) age of the patients was 70 (22–94) years, and the majority (60.4%) received pembrolizumab as first‐line therapy. The most common type of melanoma was cutaneous (41.5%), followed by mucosal (29.3%), acral (24.8%), and unknown (4.4%). Overall, 45.2% and 24.8% of patients experienced TRAEs and AEOSIs, respectively. In total, 24.8% and 9.2% of patients experienced any‐grade and grade ≥3 pembrolizumab‐related AEOSIs, respectively. The most common grade ≥3 pembrolizumab‐related AEOSIs were endocrine disorders and liver dysfunction (2.4% each), followed by colitis/severe diarrhea (2.0%), interstitial lung disease (1%), and type 1 diabetes (0.7%). No grade 5 J‐AEOSIs were observed. ORR was 16.5% at the 1‐year follow‐up: mucosal melanoma (20%), acral melanoma (10%), and cutaneous melanoma (17.5%). ORR was higher among patients who did not receive versus those who did receive previous systemic therapy across all three melanoma types. DCR was 52.1% at the 1‐year follow‐up: cutaneous melanoma (57.3%), acral melanoma (51.7%), and mucosal melanoma (43.1%). This all‐case PMS survey confirmed the real‐world safety and effectiveness of pembrolizumab monotherapy for the treatment of radically unresectable melanoma in Japan.